The neuron-derived orphan receptor 1 (NOR1) is induced upon human alternative macrophage polarization and stimulates the expression of markers of the M2 phenotype. Issue 1 (July 2015) - De Paoli, F.; Eeckhoute, J.; Copin, C.; Vanhoutte, J.; Duhem, C.; Derudas, B.; Dubois-Chevalier, J.; Colin, S.; Zawadzki, C.; Jude, B.; Haulon, S.; Lefebvre, P.; et al.
Abstract: Background: Atherosclerosis is an inflammatory disease in which macrophages play a crucial role. Macrophages are present in different phenotypes, with at the extremes of the spectrum the classical M1 pro-inflammatory and the alternative M2 anti-inflammatory macrophages. The neuron-derived orphan receptor 1 (NOR1), together with Nur77 and Nurr1, are members of the NR4A orphan nuclear receptor family, expressed in human atherosclerotic lesion macrophages. However, the role of NOR1 in human macrophages has not been studied yet. Objectives: To determine the expression and the functions of NOR1 in human alternative macrophages. Methods and results: In vitro IL-4 polarization of primary monocytes into alternative M2 macrophages enhances NOR1 expression in human but not in mouse macrophages. Moreover, NOR1 expression is most abundant in CD68+MR+ alternative macrophage-enriched areas of human atherosclerotic plaques in vivo . Silencing NOR1 in human alternative macrophages decreases the expression of several M2 markers such as the Mannose Receptor (MR), Interleukin-1 Receptor antagonist (IL-1Ra), CD200 Receptor (CD200R), coagulation factor XIII A1 polypeptide (F13A1), Interleukin 10 (IL-10) and the Peroxisome Proliferator-Activated Receptor (PPAR)γ. Bioinformatical analysis identified F13A1, IL-1Ra, IL-10 and the Matrix Metalloproteinase-9 (MMP9) as potential target genes of NOR1 in human alternative macrophages. Moreover, expression and enzymatic activity of MMP9 are induced by silencing and repressed by NOR1 overexpression in M2 macrophages. Conclusions: These data identify NOR1 as a transcription factor induced during alternative differentiation of human macrophages and demonstrate that NOR1 modifies the alternative macrophage phenotype. Highlights: Expression and immunohistological studies show that NOR1 is induced in human alternative macrophages in vitro and in atherosclerotic plaques. Silencing experiments with different siRNA show that NOR1 controls alternative macrophage phenotype by increasing the expression of M2 markers. Silencing and overexpression experiments show that NOR1 decreases expression and activity of MMP9, an M1 marker involved in plaque vulnerability.